Politics as a game: the main psychological attitude - Polikarpov, Vladimir A. (Journal of the Belarusian State University. Sociology, 2019)
Revealed the secret of power. It lies in the psychological plane. Power is possible only if there is agreement to obey the governed subjects. All decisions made by the authorities are made subject to obtaining this consent. Violation of this principle leads to the loss of power. Political relations are presented as a game with a playing field, pieces for the game and certain rules. This allows us to extremely simplify the subject and simplifies the task of computer modeling of political processes.
Keywords: the game; the rules of the game; the conditions of the game; social relations; political relations; the aggregate subject of political action; the substantial stream; the generating stream; utopia; dystopia; power; the consent of the substantial stream